2018
DOI: 10.1155/2018/9643083
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Fetal, and Neonatal Outcomes in Pregnant Dengue Patients in Mexico

Abstract: To increase our understanding of the consequences of dengue virus infection during pregnancy, a retrospective analysis was performed on the medical records of all completed pregnancies (live births and pregnancy losses) at nine public hospitals in the Gulf of Mexico from January to October 2013. Eighty-two patients developed clinical, laboratory-confirmed dengue virus infections while pregnant. Of these, 54 (65.9%) patients were diagnosed with dengue without warning signs, 15 (18.3%) patients were diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
1
29
0
3
Order By: Relevance
“…In our study, we found that 29% of women with dengue had preterm births and low birthweight infants, which is consistent with recent reviews reporting these factors as the 2 most common adverse pregnancy outcomes (9). Although 9 (21%) infants had head circumferences less than the third percentile, this finding was not associated with maternal dengue infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we found that 29% of women with dengue had preterm births and low birthweight infants, which is consistent with recent reviews reporting these factors as the 2 most common adverse pregnancy outcomes (9). Although 9 (21%) infants had head circumferences less than the third percentile, this finding was not associated with maternal dengue infection.…”
Section: Discussionsupporting
confidence: 92%
“…Immunologic changes that occur in mid-to-late pregnancy could lead to an increase in the risk for severe dengue if infections occur during pregnancy (9,36,37). In our study, women were screened mainly during the second and third trimesters because the woman usually come for antenatal care during that period.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women face potential complications from infection with either dengue or Zika virus (72). Dengue virus infection might increase the risk for maternal death or obstetric complications (e.g., hemorrhage, preeclampsia, eclampsia, and vertical transmission) during the peripartum period (73)(74)(75). Zika virus infection during pregnancy can result in fetal loss, microcephaly, or serious birth defects including structural abnormalities of the brain and eye (30,72).…”
Section: Clinical and Epidemiologic Criteria For Testingmentioning
confidence: 99%
“…Observation in present study was similar to the study by Carlos et al, wherein they reported maternal mortality in 5 cases all had been diagnosed with severe dengue infection, this observation was similar to present study. 17 Old studies report an association between low birth weight babies and dengue infection, with most of LBW attributed to prematurity. [11][12][13] In present study, authors had 4 (11.1%) LBW babies and there were 17 (47.2%) premature babies which was more compared to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%